2010
DOI: 10.1097/prs.0b013e3181c91d27
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Tissue Expander Reconstruction of Burned and Unburned Chest and Breasts Using Endoscopic and Open Techniques

Abstract: The authors believe that breast and chest burn deformities can be safely reconstructed with tissue expanders without increased complications over expander reconstruction of the congenital breast. Furthermore, endoscopic techniques may be superior for burn deformities because of improved visualization and remote incisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…32 Remote incision, far from the stress of the expansion, also minimizes the chances of wound dehiscence. 12 Whether the risks of extrusion and de ation can be reduced by the endoscopic technique remain controversial. [11][12][13] Although the use of an endoscope reduces the length of surgical incision, the pockets for expander placement are not narrowed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Remote incision, far from the stress of the expansion, also minimizes the chances of wound dehiscence. 12 Whether the risks of extrusion and de ation can be reduced by the endoscopic technique remain controversial. [11][12][13] Although the use of an endoscope reduces the length of surgical incision, the pockets for expander placement are not narrowed.…”
Section: Discussionmentioning
confidence: 99%
“…12 Whether the risks of extrusion and de ation can be reduced by the endoscopic technique remain controversial. [11][12][13] Although the use of an endoscope reduces the length of surgical incision, the pockets for expander placement are not narrowed. According to our experience in expander placement by both the endoscopic method and the open method, appropriate and uniform dissection of the plane depends on the degree of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…32 Remote incision, far from the stress of the expansion, also minimizes the chances of wound dehiscence. 12 Whether the risks of extrusion and de ation can be reduced by the endoscopic technique remain controversial. [11][12][13] Although the use of an endoscope reduces the length of surgical incision, the pockets for expander placement are not narrowed.…”
Section: Discussionmentioning
confidence: 99%
“…Some early studies reported that endoscopy-assisted expander placement requires a longer operative time, 27,28 but this was disproved by later research that showed that the endoscopic technique could signi cantly shorten placement time, especially when more than one expander had to be placed. [11][12][13]15 We believe that the contradictory conclusions were due to differences in the pro ciency of the surgeons in endoscopic operation. The small and remote incision, and the earlier initiation of expansion, all contribute to shorten hospital stay and time to full expansion.…”
Section: Discussionmentioning
confidence: 99%
“…An effective method of reconstruction can be accomplished with expansion of adjacent healthy tissue and serial transfer to replace the hypertrophic scar. For this purpose, tissue expanders can be placed through the scar or using minimally invasive endoscopic techniques which have been demonstrated to minimize associated complications [63]. …”
Section: Managementmentioning
confidence: 99%